2019
DOI: 10.5888/pcd16.180582
|View full text |Cite
|
Sign up to set email alerts
|

Multisector Approach to Improve Healthy Eating and Physical Activity Policies and Practices in Early Care and Education Programs: The National Early Care and Education Learning Collaboratives Project, 2013–2017

Abstract: Purpose and Objectives Embedding healthy eating and physical activity best practices in early care and education settings is important for instilling healthy behaviors early in life. A collaborative partnership between Nemours Children’s Health System and the Centers for Disease Control and Prevention was created to implement the National Early Care and Education Learning Collaboratives Project (ECELC) in childcare settings in 10 states. We measured improvement at the program level by the self-rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Several trials targeting the improvement of ECEC nutrition practices have included both practices to be implemented (e.g., praise children for trying new foods, role model eating healthy foods) as well as de-implemented (e.g., requiring children to sit at the table until they clean their plates, using food to encourage appropriate behaviour) [ 31 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ]. Many of such studies have reported promising results on the implementation [ 81 , 82 ], however, without a distinct de-implementation lens, little can be concluded about effective de-implementation strategies from such trials [ 83 ]. Specifically, trials that consider de-implementation when designing interventions (i.e., when choosing theories, strategies and strategy mechanisms), differentiate de-implementation aims from any implementation aims, and measure outcomes in the context of de-implementation, are required [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several trials targeting the improvement of ECEC nutrition practices have included both practices to be implemented (e.g., praise children for trying new foods, role model eating healthy foods) as well as de-implemented (e.g., requiring children to sit at the table until they clean their plates, using food to encourage appropriate behaviour) [ 31 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ]. Many of such studies have reported promising results on the implementation [ 81 , 82 ], however, without a distinct de-implementation lens, little can be concluded about effective de-implementation strategies from such trials [ 83 ]. Specifically, trials that consider de-implementation when designing interventions (i.e., when choosing theories, strategies and strategy mechanisms), differentiate de-implementation aims from any implementation aims, and measure outcomes in the context of de-implementation, are required [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study of 1173 early education and care programs across 10 states of the US, from 2012–2017, found that a multisector approach to promoting policies and practices related to child nutrition could lead to improved food environments for young children in childcare settings [ 65 ]. They developed consistent, centralised supporting materials and allowed for tailoring in the approach by individual services, similar to our proposal of harmonisation.…”
Section: Discussionmentioning
confidence: 99%
“…They developed consistent, centralised supporting materials and allowed for tailoring in the approach by individual services, similar to our proposal of harmonisation. That study demonstrated that collaborative partnerships led to broad implementation of best practices in relation to child nutrition and that this model was found to be complementary rather than duplicative to existing programs and initiatives [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The larger Heart Disease and Stroke Prevention Learning Collaborative, a cooperative agreement between the Association of State and Territorial Health Officials and the Centers for Disease Control and Prevention (CDC) (9), used a systems change framework, teams, and expanded self-management options and found them effective, including in rural settings. CDC supported state collaboratives with child care resource and referral networks in 10 states (10), tested methods of supporting adoption of best practices, and found improvements overall, suggesting that it may be the partnerships themselves, in addition to the programs, that make a difference. Over time, linkages can become extensive and strong, as has been the case in Nebraska (11), requiring effective management and continued attention to ensure community priorities remain paramount.…”
mentioning
confidence: 99%
“…The evaluation methods reported are striking for the predominance of mixed methods; the use of diverse data sources, including commercial health claims data sets (15,16), electronic health records (4), geotags (16), and new measures such as Facebook click-through rates (13); the use of well-established frameworks such as RE-AIM (Reach, Effectiveness, Adoption, Implementation, Maintenance) (4); and for their high level of sophistication (10). Although it is possible to use simple evaluation methods when assessing the value of single components of a larger program (such as the comparative value of different social media methods [13]), evaluation of large, complex programs requires considerable expertise, planning time, and funding.…”
mentioning
confidence: 99%